Peningkatan Kemahiran Berbahasa Indonesia melalui Program Klinik Bahasa UKBI Adaptif - Pandu Meidian Pratama (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2021)
The Indonesian Language Proficiency Test (UKBI) is one of the Indonesian language proficiency tests that aims to measure written and oral proficiency, both by spoken and foreign speech. In its development, UKBI developed into an adaptive UKBI which can display different levels of question difficulty for each examiner, so that UKBI has a variety of questions that are not the same between participants and a different number of questions. The method used in this research is a simple qualitative and quantitative descriptive method with primary data obtained through survey results. The results in this study were that of the 51 participants who took part in the activity, 30 of them took part in the UKBI simulation activity with the lowest UKBI simulation score being 60 and the highest being 100. After attending the language clinic, the participants who were very interested in taking the UKBI test visited 15 people, interested in participating in the UKBI test. opened 16 people, and less interested in opening 2 people or 92%.